2012
DOI: 10.1242/jcs.096826
|View full text |Cite
|
Sign up to set email alerts
|

Plo1 phosphorylates Dam1 to promote chromosome bi-orientation in fission yeast

Abstract: SummaryThe fungal-specific heterodecameric outer kinetochore DASH complex facilitates the interaction of kinetochores with spindle microtubules. In budding yeast, where kinetochores bind a single microtubule, the DASH complex is essential, and phosphorylation of Dam1 by the Aurora kinase homologue, Ipl1, causes detachment of kinetochores from spindle microtubules. We demonstrate that in the distantly related fission yeast, where the DASH complex is not essential for viability and kinetochores bind multiple mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Similarly, mutations in budding yeast motor proteins, such as Kar3 (kinesin-14 family protein, Klp2 in S. pombe), Cin8, Kip1 (kinesin-5 family protein) and Kip3 (kinesin-8 family protein, Klp5/Klp6 in S. pombe) involved in MT stability, also display changes in spindle length (Straight et al, 1998;Zeng et al, 1999). Further, Dam1 plays a role in correct kinetochore attachments and bi-orientation in budding as well as fission yeast, lack of which leads to activation of the spindle assembly checkpoint (SAC), delaying the onset of anaphase (Janke et al, 2002;Sanchez-Perez et al, 2005;Buttrick et al, 2012). Dam1 phosphorylation by frequency of invasive hyphae at 36-40 hpi on rice leaf sheaths in the dam1Δ compared to the WT strain from three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mutations in budding yeast motor proteins, such as Kar3 (kinesin-14 family protein, Klp2 in S. pombe), Cin8, Kip1 (kinesin-5 family protein) and Kip3 (kinesin-8 family protein, Klp5/Klp6 in S. pombe) involved in MT stability, also display changes in spindle length (Straight et al, 1998;Zeng et al, 1999). Further, Dam1 plays a role in correct kinetochore attachments and bi-orientation in budding as well as fission yeast, lack of which leads to activation of the spindle assembly checkpoint (SAC), delaying the onset of anaphase (Janke et al, 2002;Sanchez-Perez et al, 2005;Buttrick et al, 2012). Dam1 phosphorylation by frequency of invasive hyphae at 36-40 hpi on rice leaf sheaths in the dam1Δ compared to the WT strain from three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the Ser20 residue of Dam1 disrupts its binding to the Ndc80 complex (Tien, et al 2010) while phosphorylation of C-terminal residues compromises Dam1 oligomerization (Wang, et al 2007). Although phosphorylation-mediated regulation of Dam1 does not seem to be conserved in fission yeast (Buttrick, et al 2012), in higher eukaryotes Aurora B-mediated phosphorylation negatively regulates kinetochore-localization and microtubule binding of the Ska complex, which has very similar functions as the Dam1 complex despite no apparent structural similarity (Jeyaprakash, et al 2012). The Ska complex binds to the Ndc80 complex and supports kinetochore-microtubule attachment by providing affinity for curved protofilaments, which facilitates binding to depolymerizing microtubules (Chan, et al 2012; Schmidt, et al 2012).…”
Section: Phosphorylations That Control Kinetochore-microtubule Attachmentioning
confidence: 99%
“…This observation contrasts with a forced Cdc5 localization to both Cse4, which caused a strong growth inhibition but did not accumulate cells at any specific stage of the cell cycle [ 27 ], and to the DAM1/DASH1 subunit Dad4, which accumulated cells later in the cell cycle, possibly in late anaphase and/or telophase ( S4 Fig ). Notably, in fission yeast, it has been reported that Polo kinase, Plo1, phosphorylates Dam1 during prometaphase and metaphase for faithful chromosome biorientation [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…cycle, possibly in late anaphase and/or telophase (S4 Fig). Notably, in fission yeast, it has been reported that Polo kinase, Plo1, phosphorylates Dam1 during prometaphase and metaphase for faithful chromosome biorientation [59].…”
Section: Plos Geneticsmentioning
confidence: 99%